If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x+3)=3(2x-10)
We simplify the equation to the form, which is simple to understand
2(x+3)=3(2x-10)
Reorder the terms in parentheses
+(+2x+6)=3*(2x-10)
Remove unnecessary parentheses
+2x+6=+3+*(+2x-10+)
Reorder the terms in parentheses
+2x+6=+(+6x-30)
Remove unnecessary parentheses
+2x+6=+6x-30
We move all terms containing x to the left and all other terms to the right.
+2x-6x=-30-6
We simplify left and right side of the equation.
-4x=-36
We divide both sides of the equation by -4 to get x.
x=9
| -11x-8+3x=24 | | 2(-7x+6)=-16-7x | | 5.9x=-30.09 | | -5=7+4x | | 2c+3=4(5c-6) | | 4(2x+3)+5=1 | | -5x-4(-7-4x)=36+7x | | 60=4(5-x) | | 2(5+x)=-30 | | x-21=-x*2 | | 3(7x-7)=-6+6x | | 4x-148=3x+566 | | 50+0.9*(y-30)+10+10+28=y | | 5[2-3(x-8)]=26-8x | | (2x^4)+16x=0 | | 2x+(-4x)=22 | | 4x+9-49=0 | | -1+3(v-7)=-28 | | 2x^2+22x+60=x | | 20y+13=15y-8 | | 4x+4x=64 | | (18a^3)-72a=0 | | z-0.45=5.97 | | 3a+(4b+2)I=9-6I | | 50+0.9*(y-30)=y | | -5x+24=-8(x-6)+6x | | -(-a)= | | 3x(4)=2 | | -n+n= | | 2(4z-2)-2(5-3z)=4 | | 5x+5=4x+4 | | 11+2(3n-11)=1 |